2020
DOI: 10.15869/itobiad.648827
|View full text |Cite
|
Sign up to set email alerts
|

CAMELS Değerlendirme Sistemiyle Bankaların Finansal Performanslarının TOPSİS Yöntemiyle Analizi

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and confirmed to include no plagiarism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Thereupon, the weight scores of the criteria are determined according to the objective or subjective weighting method to be used in the study. Unlike the previous studies found in the literature, i.e., Keçek and Cinser (2008), Ertuğrul and Karakaşoğlu (2009), Ustasüleyman (2009), Demireli (2010), Dai and Wang (2011), Uygurtürk and Korkmaz (2012), Bağcı and Rençber (2014) ), Mandic et al (2014), Çelen (2014a), Çelen (2014b), Saldanlı and Sırma (2014), Kandemir and Karataş (2016), Wanke et al (2016), Beheshtinia and Omidi (2017), Yıldırım and Demirci (2017), Gökmen Özkan (2017), Yamaltdinova (2017), Kalıntaş and Özarı (2019), Arslan (2019), Kendirli et al (2019), Karakaya (2019), Aydın (2020), Daver (2020), Kaygusuz et al (2020), Gökmen Özkan and Deliktaş (2020), Gülençer (2020), Sarı (2020), Tuba Özkan (2020), Yılmaz (2020), Gül (2021), Gülsün and Erdoğmuş (2021), Türegün (2022) , Baydas (2022), Wanke et al (2022), CRITIC-TOPSIS (CRT) was used in this study to calculate the performance scores of the banks, which are the subject of the research, in the pre-2019 and during 2020 year of COVID-19 and to obtain their ranking according to these scores, whereas Mean Weight-TOPSIS (MWT) and Entropy-TOPSIS (ENT) hybrid methods are applied separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereupon, the weight scores of the criteria are determined according to the objective or subjective weighting method to be used in the study. Unlike the previous studies found in the literature, i.e., Keçek and Cinser (2008), Ertuğrul and Karakaşoğlu (2009), Ustasüleyman (2009), Demireli (2010), Dai and Wang (2011), Uygurtürk and Korkmaz (2012), Bağcı and Rençber (2014) ), Mandic et al (2014), Çelen (2014a), Çelen (2014b), Saldanlı and Sırma (2014), Kandemir and Karataş (2016), Wanke et al (2016), Beheshtinia and Omidi (2017), Yıldırım and Demirci (2017), Gökmen Özkan (2017), Yamaltdinova (2017), Kalıntaş and Özarı (2019), Arslan (2019), Kendirli et al (2019), Karakaya (2019), Aydın (2020), Daver (2020), Kaygusuz et al (2020), Gökmen Özkan and Deliktaş (2020), Gülençer (2020), Sarı (2020), Tuba Özkan (2020), Yılmaz (2020), Gül (2021), Gülsün and Erdoğmuş (2021), Türegün (2022) , Baydas (2022), Wanke et al (2022), CRITIC-TOPSIS (CRT) was used in this study to calculate the performance scores of the banks, which are the subject of the research, in the pre-2019 and during 2020 year of COVID-19 and to obtain their ranking according to these scores, whereas Mean Weight-TOPSIS (MWT) and Entropy-TOPSIS (ENT) hybrid methods are applied separately.…”
Section: Methodsmentioning
confidence: 99%
“…In their study, Kaygusuz et al (2020) used the TOPSIS method with which they tried to examine the Camels valuation system components and bank performance. This study encompassed ten banks with ten years of data, with Denizbank to be the bank with the highest performance, and Halkbank as the bank with the lowest performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…B) The summaries provided below are the studies in the performance of banks using TOPSIS method; Sarı, (2020), Kaygusuz, et al (2020), Bozdoğan, et al (2018), Anyaeche et al (2018), Siew et al (2017), Wanke et al (2017), Wanke et al (2016, Dash (2016), Ghasempour et al (2016), Li et al (2014), Amile et al (2013), Hemmati et al (2013), Akkoç et al (2013), Dinçer et al (2011), Demireli (2010 and Seçme et al (2009) these studies have been done for the evaluation of banks performances with TOPSIS method.…”
Section: Literature Reviewmentioning
confidence: 99%